Exceptionally high thermal and electrical conductivity of three-dimensional graphene-foam-based polymer composites. Issue 27 (25th February 2016) - Liu, Zhiduo; Shen, Dianyu; Yu, Jinhong; Dai, Wen; Li, Chaoyang; Du, Shiyu; Jiang, Nan; Li, Hairong; Lin, Cheng-Te
Abstract : Three dimensional graphene foam incorporated into epoxy matrix greatly enhance its thermal conductivity (up to 1.52 W mK −1 ) at low graphene foam loading (5.0 wt%), over an eight-fold enhancement in comparison with that of neat epoxy. Abstract : Graphene foams (GF) assembled with one- or few-layered ultrathin two-dimensional crystals have showed huge application potentials owing to their unique three-dimensional (3D) structure and superior properties. Here, we present a polymer-template-assisted assembly strategy for fabricating a novel class of 3D graphene architecture. A free-standing GF architecture has been built to act as thermal and electrical conduction paths in polymer composites. The obtained GF/polymer composites exhibit a high thermal conductivity (1.52 W mK −1 ) and high electrical conductivity (3.8 × 10 −2 S cm −1 ) at relatively low GF loading (5.0 wt%). The GF/polymer composites are potentially useful in advanced packaging materials of high power LED and microelectronic devices.